2016
DOI: 10.3390/beverages2040028
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ethyl Carbamate Contamination in Cachaça (Brazilian Sugar Cane Spirit)

Abstract: Cachaça is a sugar cane spirit produced in Brazil. Ethyl carbamate (EC), a potential carcinogenic compound, may be present in cachaça above the limit established by law. The purpose of this study was to determine the concentration of ethyl carbamate in cachaças recently produced in Brazil in order to verify their compliance with the law. The concentration of ethyl carbamate was determined in 376 samples of cachaça through gas chromatography coupled to a mass spectrometer (GC-MS). The mean value of ethyl carbam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Nowadays, methods to analyze EC are mainly based on gas chromatography-mass spectrometry (GC-MS) and related methods. [8][9][10][11][12][13] The limitations of these methods are high cost, complex sample pre-treatment and complex operation. 8,14 At present, it is difficult to separate and analyze EC due to low concentrations in samples and due to its low molecular weight.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, methods to analyze EC are mainly based on gas chromatography-mass spectrometry (GC-MS) and related methods. [8][9][10][11][12][13] The limitations of these methods are high cost, complex sample pre-treatment and complex operation. 8,14 At present, it is difficult to separate and analyze EC due to low concentrations in samples and due to its low molecular weight.…”
Section: Introductionmentioning
confidence: 99%
“… 8–13 The limitations of these methods are high cost, complex sample pre-treatment and complex operation. 8,14 At present, it is difficult to separate and analyze EC due to low concentrations in samples and due to its low molecular weight. Therefore, it is today very relevant to study the enrichment, separation and detection of EC.…”
Section: Introductionmentioning
confidence: 99%
“…For chemical contamination, a Gas Chromatography Mass Spectroscopy (GC-MS) technique was used following a method modified from Bortoletto and Alcarde (2016). A standard curve for ethyl carbamate (EC) and furfural (FR) was established to quantify the concentration of both these chemicals (Figure 2).…”
Section: Determination Of Ethyl Carbamate and Furfural By Gc-msmentioning
confidence: 99%
“…8,9 The permitted concentration of ethyl carbamate in sugar cane spirit was increased in 2014 from 150 to 210 µg L -1 . 10 Ethyl carbamate levels are defined in Brazil by the Ministry of Agriculture, Livestock and Food Supply (MAPA), the Brazilian Regulation Agency for Food Control. 11 Early studies showed that cyanogenic compounds, such as the amino acid arginine and urea, form cyanide ions which are the precursors of ethyl carbamate in the fermentation process.…”
Section: Introductionmentioning
confidence: 99%
“…1 These nitrogen-containing compounds in high temperatures and acid medium of the distillation form cyanide ions, which triggers the formation of ethyl carbamate. 10 There are two alternative formation pathways for ethyl carbamate, one towards copper ion interactions with cyanide ions, forming a cyanate anion, and the subsequent reaction with ethanol, and another via the auto-oxidation of cyanide to cyanate, which forms ethyl carbamate with ethanol. 12 The pressing concern of the levels of ethyl carbamate in sugar cane spirits in commercial products has led researchers to develop alternatives to reduce the levels of fermented drinks.…”
Section: Introductionmentioning
confidence: 99%